2017
DOI: 10.1038/leu.2017.245
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib-induced vasculopathy: identification of vascular endothelial cells as a primary target site

Abstract: The BCR/ABL1 inhibitor Nilotinib is increasingly used to treat patients with chronic myeloid leukemia (CML). Although otherwise well-tolerated, Nilotinib has been associated with the occurrence of progressive arterial occlusive disease (AOD). Our objective was to determine the exact frequency of AOD and examine in vitro and in vivo effects of Nilotinib and Imatinib on endothelial cells to explain AOD-development. In contrast to Imatinib, Nilotinib was found to upregulate pro-atherogenic adhesion-proteins (ICAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 43 publications
4
90
0
Order By: Relevance
“…The pathophysiological mechanisms underlying the vascular toxicity of TKIs have not been clearly established but are believed to overlap to some extent. In a mouse model of atherosclerosis, nilotinib was shown to have directly proatherogenic effects on endothelial cells [42]. Nilotinib also caused metabolic changes including elevation of cholesterol and fasting glucose levels [42].…”
Section: Safety Profilementioning
confidence: 99%
“…The pathophysiological mechanisms underlying the vascular toxicity of TKIs have not been clearly established but are believed to overlap to some extent. In a mouse model of atherosclerosis, nilotinib was shown to have directly proatherogenic effects on endothelial cells [42]. Nilotinib also caused metabolic changes including elevation of cholesterol and fasting glucose levels [42].…”
Section: Safety Profilementioning
confidence: 99%
“…These include increased fasting glucose, type 2 diabetes mellitus, and increased total high density and low density lipoprotein cholesterol. Nilotinib also interferes with endothelial cell migration, cell proliferation, and promotes a pro-atherogenic phenotype by increasing the expression of cell surface adhesion molecules 7. A recent paper revealed multiple pathways through which Nilotinib encourages a prothrombotic state 8.…”
Section: Discussionmentioning
confidence: 99%
“…Although these TKIs have been reported to be well tolerated during long‐term treatment, recent studies have demonstrated that severe vascular events, such as coronary artery disease (CAD), cerebral ischemic disease, and peripheral artery occlusive disease, have developed in some patients receiving each TKI . The exact mechanisms for development of vascular events during treatment of TKIs remain unclear, but recent data suggested that the direct effects of vascular endothelial cells on TKIs might contribute to the development of vascular events …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The exact mechanisms for development of vascular events during treatment of TKIs remain unclear, but recent data suggested that the direct effects of vascular endothelial cells on TKIs might contribute to the development of vascular events. [3][4][5] Atherosclerosis is characterized as vascular inflammation involving endothelial cells, smooth muscle cells, lymphocytes, and monocytes/ macrophages. The inflammatory response for development of atherosclerosis is mainly associated with recruitment and activation of monocytes and monocyte-derived macrophages on atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%